Effect of continuous intravenous oxycodone infusion in opioid-naïve cancer patients with dyspnea. (11th June 2018) - Yamamoto, Yoshihiro; Watanabe, Hiroaki; Sakurai, Aina; Deguchi, Yuko; Hirano, Shigeki; Okumura, Yoshimi; Kumon, Akiko; Watanabe, Norio; Osada, Takashi; Yamamura, Keiko; Odagiri, Takuya
Abstract : This study demonstrated the efficacy and safety of continuous oxycodone infusion for opioid-naïve cancer patients with dyspnea. Oxycodone infusion could be a reasonable treatment option in the management of dyspnea in these patients. Abstract: Aim: Dyspnea is among symptoms that decrease quality of life for terminal cancer patients. There are few reports of the positive effects of oxycodone for the treatment of dyspnea, and no studies have focused on opioid-naïve patients. This study aimed to determine the efficacy and safety of continuous intravenous oxycodone infusion for opioid-naïve cancer patients with dyspnea. Methods: Eligible patients were opioid-naïve cancer inpatients who received continuous oxycodone infusion as a treatment for dyspnea under the care of the palliative care team at Komaki City Hospital between November 2013 and December 2016. We retrospectively investigated the improvement of dyspnea following continuous oxycodone infusion from the medical records. Results: This study included 19 patients, and the response rate to oxycodone infusion for dyspnea was 68.4%. Most participants were terminal cancer patients with performance status 3 or 4. Median survival of participants following continuous oxycodone infusion was 6 (range 1–377) days. No serious adverse events such as respiratory depression or somnolence were noted. Conclusion: Continuous oxycodone infusion could be a reasonable treatment option in the management of dyspnea in opioid-naïve cancer patients.